PENGARUH KONFLIK PERAN, KETIDAKJELASAN PERAN, EFIKASI DIRI TERHADAP KINERJA AUDITOR DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada Kantor Akuntan Publik di Pekanbaru, Padang, Batam) - Nadiah Ocvinitha Rahman; Hardi Hardi; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study was aimed to examine the influence of Role Conflict, RoleAmbiguity, Self - Efficacy to Auditors Performance With Emotional Quotient AsModerating Variabele (Empirical Study On Representation Of Auditor At Pekanbaru,Padang, Batam) The respondent are in the analysis were 64 respondents. Thestudy used primary data which was obtained from the answer of the respondentsand the questionnaire distributed. The collected data was analyzed using dataanalysis method by firstly proposing the classical assumption before performingthe hypothesis test. Classical assumption test and hypothesis test was done usingSPSS software version 23 for Windows. The hypothesis test in this research usedmultiple regression linier with t-test at significance level 5 % (α = 0 ,0 5),moderated regression analysis and determination coefficient test. The result of thestudy found that Role conflct significanly influence to auditors performance , roleambiguty significanly influence to auditors performance, self – efficacysignificanly influence to auditors performance. Emotional quotient is amoderating variable between influence of role conflict, role ambiguity to auditorsperformance but it cannot be moderating between self - efficacy to auditorsperformance.Keywords : role conflict, role ambiguity, self – efficacy, emotionl quotient, auditorperformance.